Keratosis follicularis (Darier disease) – clinical characteristics and treatment – a review and update - Chyl-Surdacka, Katarzyna; Borzęcki, Adam; Latifa, Jakub; Turska-Kozłowska, Monika; Majchrzycka, Marianna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2023)
Darier disease is one of the most common genodermatoses. Although Darier disease was described in 1886, targeted therapies remain unknown. Current literature lacks specific guidelines for treatment of Darier disease. Treatment remains symptomatic and may be challenging for dermatologists. The aim of this article is to present clinical characteristics and treatment options. In a mild form of the disease with a small number of skin lesions, the symptoms can be reduced by the use of topical medications. Oral retinoids, alternatively doxycycline, seem to be beneficial in extensive and persistent lesions unresponsive to local treatment. In limited, hypertrophic forms, surgical methods, laser therapy and photodynamic therapy could be used.